Traditional Chinese Medicine Injections Combined With Antihypertensive Drugs for Hypertensive Nephropathy: A Network Meta-Analysis - Chen, Zhe; Peng, Yingying; Yang, Fengwen; Qiang, Xiaoyu; Chen, Yong; Chen, Yongjie; Cao, Lujia; Liu, Chunxiang; Zhang, Junhua (Frontiers in Pharmacology, 2021)
Background: Hypertensive nephropathy (HN) was hazardous to physical fitness and healthy body mass and even caused economic burdensome. Traditional Chinese medicine injections (TCMIs) combined with antihypertensive drugs (ADs) as the therapeutic option for HN. Thus, we evaluated the efficacy and safety of various TCMOIs combine with ADs for patients with HN firstly. Methods: We conducted a comprehensive search of secen databases from inception until May 2021 to select the randomized controlled trials (RCTs). Literature screening, data extraction, and quality assessment independently by two reviewers with the same criteria. We performed the effect modeling to analyze the data for all outcomes and ranked each intervention by P-score. Further, sensitivity analysis, meta-regression, and funnel plots have been conducted to test the stability, heterogeneity, and publication bias, respectively. Results: We included 69 RCTs with 6373 patients in this systematic review, including six TCMIs combined with ADs (TCMIs+ADs). Network analysis results showed that ginkgo leaf extract and dipyridamole combined with ADs (GLED+ADs) were more efficacious to treat HN than other interventions in the 24-hour urinary protein excretion (mean difference [MD] = -0.70, 95% credible interval [CI]: -0.82 to -0.58) and systolic blood pressure (MD =-12.95, 95% CI: -10.55 to -3.21) with P-score 1 and 0.88. Salvianolate combined with ADs (SA+ADs) was the highest effectiveness for the diastolic blood pressure (MD =-6.88, 95% CI: -10.55 to -3.21) with a P-score of 0.9. Based on the combined P-score of network meta-analysis results (88% and 85.26%) and sensitivity analysis results (72% and 71.54%), biplots showed that GLED+ADs were the best most efficacious intervention in all TCMIs+ADs for primary outcomes, follow by SA+ADs and sodium tanshinone IIA sulfonate combined with ADs (STS+ADs). There was no significant difference in terms of safety between TCMIs+ADs and ADs. Conclusion: In all TCMIs+ADs, GLED+ADs, SA+ADs, and STS+ADs may demonstrate better efficaciousness than ADs for HN, and GLED+ADs with the highest combined P-score may be the best option. Due to the absence of safety evidence and other limitations, we should use various TCMIs with caution in clinical practice. More high-quality trials should be conducted from the clinical standpoint of patients and professionals.